Diagnosis of Early Pancreas Graft Failure via Antibody‐Mediated Rejection: Single‐Center Experience With 256 Pancreas Transplantations. Issue 4 (12th February 2014) - de Kort, H.; Mallat, M. J. K.; van Kooten, C.; de Heer, E.; Brand‐Schaaf, S. H.; van der Wal, A. M.; Roufosse, C.; Roelen, D. L.; Bruijn, J. A.; Claas, F. H.; de Fijter, J. W.; Bajema, I. M.
<x xml:space="preserve">Abstract</x> Early pancreas graft loss is usually attributed to technical failure while the possibility of antibody‐mediated rejection (AMR) is generally overlooked. To investigate the role of AMR in early pancreas graft loss, we retrospectively assessed 256 patients with simultaneous pancreas–kidney transplantation (SPK) between 1985 and 2010 at our institute. We included 33 SPK patients who lost their pancreas graft <1 year after transplantation. AMR was diagnosed based on donor‐specific antibodies, C4d and histology in 7 cases, 8 cases were suspicious for AMR and 18 pancreas graft losses were not due to AMR. Acute AMR occurred >1 month after transplantation in 6/7 cases, whereas all other causes typically led to loss <1 month after transplantation. Thrombotic lesions occurred equally among the 33 cases. In 12/18 concurrent kidney specimens, the diagnostic results paralleled those of the pancreas graft. All patients with acute AMR of the pancreas graft lost their renal grafts <1 year after transplantation. In the setting of a thrombotic event, histopathological analysis of early pancreas graft loss is advisable to rule out the possibility of AMR, particularly because a diagnosis of acute AMR has important consequences for renal graft outcomes.